Green transformational leadership and employee pro-environmental behavior: The role of green thinking and green psychological climate - Fatoki, Olawale (International Journal of Management and Sustainability, 2023)
Climate change is one of the biggest challenges that the world currently faces. The generation of waste, carbon dioxide and large-scale consumption of natural resources by hotels, among others, are some of the significant contributors to climate change. Leaders and employees have a major role to play in the effectiveness of the sustainability initiatives of hotels. Therefore, it is important to understand the mechanism through which leadership can affect the green behavior of hotel employees. The purpose of this study is to examine the mediating role of green thinking (GTH) and green psychological climate (GPC) in the relationship between green transformational leadership (GTL) and employees’ pro-environmental behavior (PEB). To achieve this, the study first investigates the effect of GTL on hotel employees’ PEB. Second, it examines the mediating effects of GTH and GPC in the relationship between GTL and PEB. The study adopts a quantitative research approach, and a structured questionnaire is used to collect data from hotel employees in South African cities, who were selected via the convenience sampling method. The partial least squares structural equation modelling is used to test the hypotheses of the study. The findings reveal that GTL and PEB are significantly positively related. The mediating effects of GTH and GPC are significant. It is recommended that both management and employees should keep up to date with environmental information and implement policies and procedures to continually improve PEB.